Industrial Utilization of Grasses - Janowszky, Zsolt (Acta Agraria Debreceniensis, 2003)
The Agricultural Research and Development Institute P.U.C., Szarvas – realizing the importance of using the biomass in a number of ways – was one of the first in Europe, who began the breeding of grasses suitable for industrial utilization. The possible areas of using the energygrass – which could be called industrial grass – are the following: – Energetical use – Paper industry use – Utilization as an industrial fibrematerial – Use for feeding The aim of the breeding programme: developing the kinds of grass, which yields big drymaterial mass and suitable for industrial utilization. These kind of grass, taking soil-utilization, economicality and environmental protection, offer and ensure new marketing perspectives and employment facilities for the disadvantageous areas.